Estimation of total population size of southern elephant seals (Mirounga leonina) on Kerguelen and Crozet Archipelagos using very high-resolution satellite imagery - Laborie, Joris; Authier, Matthieu; Chaigne, Adrien; Delord, Karine; Weimerskirch, Henri; Guinet, Christophe (Frontiers in Marine Science, 2023)
Southern elephant seals (Mirounga leonina) play a pivotal role in the Southern Ocean as wide-ranging marine predators and major prey consumers within Southern Ocean marine ecosystems. Due to their circumpolar distribution and the remoteness of their habitat, large uncertainties remain about their total population sizes. This is especially true for elephant seal populations in the French Southern Territories in the southern Indian Ocean (i.e. Crozet and Kerguelen Archipelagos) as many breeding sites are inaccessible for ground censuses. Here, we present a simple and efficient approach for estimating the total elephant seal populations of the Kerguelen and Crozet Archipelagos by using very high-resolution satellite imagery (<1m resolution). Twenty-eight satellite images taken during the breeding season to count female elephant seals in inaccessible areas were used and complemented the traditional annual ground counts in accessible areas. For Kerguelen Island sectors likely to host colonies and where no satellite images were available for the breeding season, a statistical predictive model was built to estimate the most likely number of breeding females to be present on a given beach according to its physiographic characteristics. Our results show the reliability of using very high-resolution satellite images, a relatively low-cost platform, to count pinniped populations and provide the first estimation of the total southern elephant seal population for both the Kerguelen 347,995 (s e = 4,950) and Crozet 13,065 (s e = 169) Archipelagos. The combined total represents over 35% of the global elephant seal population with the Kerguelen stock being numerically equivalent to the South Georgia stock. In addition, we re-examined the population trends since the last mid-century for Kerguelen and over the last five decades for Crozet. The demographic trends of the southern Indian Ocean populations show marked growth over the last decade (5.1% and 1.6% annual growth rate for Crozet and Kerguelen respectively), particularly on Crozet where the elephant seal population has more than tripled.